Subjective Age and Dementia. Issue 2 (15th March 2017) - Jaconelli, Alban; Terracciano, Antonio; Sutin, Angelina R.; Sarrazin, Philippe; Raffard, Stéphane; Stephan, Yannick
ABSTRACT: Objective: Existing evidence indicates that a younger subjective age is a marker of successful aging, including better health and cognition. Building upon this evidence, it is likely that individuals with dementia might feel older. However, subjective evaluation of age might not be affected by dementia because these individuals tend to be anosognosic and report positive health-related quality of life. Methods: Data from two cross-sectional samples from France and the United States were used to compare the subjective age ratings of individuals with and without dementia. Results: Results from both samples revealed that individuals with dementia felt younger than their age but did not differ from the controls, even after controlling for sex, chronological age, education, and self-rated health. Conclusion: The present study suggests that there are no large differences in the subjective experience of age between healthy individuals and those with dementia.